Environmental Regulation and Employment in Resource-Based Cities in China: The Threshold Effect of Industrial Structure Transformation - Qin, Bingtao; Liu, Lei; Yang, Le; Ge, Liming (Frontiers in Environmental Science, 2022)
Resource-based cities in China face the dual pressure of environmental pollution and unemployment. Therefore, it is necessary to measure the effect of environmental regulation on employment. In this study, we constructed a nonlinear panel threshold regression model and used data from 115 resource-based prefecture-level cities to empirically examine the impact of environmental regulation on employment. The results demonstrate that there is a significant threshold effect between environmental regulation and employment in resource-based cities, regardless of whether the industrial structure is rationalized or advanced. When the levels of industrial structure rationalization and optimization exceed the corresponding threshold value, the enhancement of environmental regulation can promote employment; when the levels of industrial structure rationalization and optimization are below the threshold value, the enhancement of environmental regulation exacerbates unemployment. This paper enriches the research content of environmental regulation on employment by taking industrial structural transformation as a threshold variable, and provides useful references for rational improvement of the environmental pollution as well as unemployment in China